Transdisciplinarity (translation. a transdisciplinary journal, 2022)
Both translation studies and cultural studies have come of age. Both interdisciplines have entered a new internationalist phase, and have been moving for some time away from their more overtly parochial and Eurocentric beginnings, towards a more sophisticated investigation of the relationship between the local and the global. Both are now vast wide-ranging fields, within which there is no consensus, but neither are there radical disagreements that threaten fragmentation or destruction from within.